Two unpublished terracotta oil lamps from Marina el-Alamein in Egypt - AbdelBaset Ali AbdelFattah Saad AbdelFattah Saad (Polish Archaeology in the Mediterranean, 2019)
The two complete terracotta oil lamps published in this paper come from salvage excavations in by an Egyptian team clearing House 21 in the ancient Graeco-Roman harbor of Marina el-Alamein on the northern coast of Egypt. Both are of Alexandrian manufacture, one of the two being an imitation of an Italic relief lamp. One is decorated with a representation of Sarapis enthroned, the other with a scene of roosters fighting. Both are from the 2nd–3rd century and reflect the Alexandrian cultural tradition in the life of this ancient town.